Analisis SWOT untuk Merumuskan Strategi Pengembangan Komoditas Karet di Kabupaten Pulang Pisau, Kalimantan Tengah - Sadik Ikhsan; Artahnan Aid (Universitas Lambung Mangkurat, 2011)
Research is aimed to formulate development strategies of rubber commodity which was reasonably determined as one of leading agricultural commodities in District of Pulang Pisau. Research was done from March to August 2010. The strategies was formulated by SWOT (Strenghts, Weaknesses, Opportunities, and Threads) analysis. The important internal points represented strenghts and weaknesses as well as the points from external environment wellknown as opportunities and threats which considerably influenced existence and deveopment of rubber commodity were listed orderly in internal strategic factor analysis summary (IFAS) matrix and external strategic factor analysis summary (EFAS) matrix. The result showed that total value of the internal strategic was 6.13, and total value of the external strategic was 5.97. It concluded that rubber commodity had strategic position to be continually developed. Some of strategic measure proposed need to be implemented such as: intensification, extensification, replanting with highyielded clone, properly preparing production inputs, improving farmers’ access to financial institution, maintaining existence land for rubber, as well as maintaining and developing infrastructure to lead better market access.